ABLATION OF ICE AND SNOW - PROTECTIVE COVERINGS AND GENERAL CRITERIA FOR APPLICATION. - Stehle,N. S. (1968)
Permanent polar ice and snow areas are often used for roads, runways, and camps because of their perennial nature and the lack of land areas. Warm temperatures and high solar radiation, however, cause deterioration and ablation of these surfaces in summer during the greatest transportation activity. Protective coverings to retard deterioration and ablation of ice and snow are needed in all but dry-snow zones in polar regions. Good drainage is the most important factor in maintaining a surface in usable condition. When ablation exceeds accumulation, any protected area will become pedestalled above the surrounding ice, and loss of the protected area will occur by slumping of the edges. When accumulation exceeds ablation, protective measures will occur by slumping of the edges. When accumulation exceeds ablation, protective measures are needed only during that part of the summer when ablation and deterioration occur. Of the protective coverings investigated, chipped ice is the easiest to produce and most economical to use in ice areas; however, other materials, such as gravel, sawdust, urethane foam, concrete planking, insulated metal planking, timber decking, and snow, may be more effective and economical for specific conditions. (Author)